A 3D‐Printed Guide to Assist in Sinus Slot Preparation for the Optimization of Zygomatic Implant Axis Trajectory. Issue 2 (11th January 2020) - Wang, Christina I.; Cho, Seok‐Hwan; Cho, David; Ducote, Colten; Reddy, Likith V.; Sinada, Naif
Abstract: Zygomatic implants have become a predictable treatment modality for the rehabilitation of the severely atrophic maxilla. Due to differing anatomic variations, proximity to vital anatomic structures and limited intraoperative visibility, the placement of zygomatic implants can be a difficult task; compromised implant positioning may ultimately lead to postoperative surgical and prosthetic complications. The purpose of this report is to demonstrate a technique that allows for the transfer of the sinus slot position. Ultimately, this optimizes zygomatic implant axis trajectory from preoperative prosthetic planning by using cone beam computed tomography (CBCT) and 3‐dimensional (3D) planning software to fabricate a stereolithographic 3D‐printed surgical guide.